The Impact of Digital Strategic Communication on the Effectiveness of Corporate Crisis Management and its Effect on the Corporate Image in the Digital Media Environment (The International Journal of Educational Sciences and Arts, 2026)
This study examines the role of digital strategic communication in crisis management for organizations and its impact on building the organization's public image within the evolving digital media landscape. The study employs dialogic communication theory as a theoretical framework to explain the nature of interaction between organizations and their audiences across digital platforms, particularly during crises.To achieve its objectives, the study utilized a quantitative approach, employing a questionnaire as the primary data collection tool from a sample of social media users in Dammam, Saudi Arabia.The study aimed to identify the relationship between digital strategic communication and the effectiveness of organizational crisis management, as well as its impact on the public's perception of organizations. The results demonstrated a clear positive correlation between digital strategic communication and effective crisis management. Furthermore, the study revealed that an organization's success in managing its crises directly translates into improved public image. The findings also indicated that digital strategic communication not only supports crisis management but can also directly influence the organization's public image by fostering interaction with the public and providing accurate, clear, and transparent information during a crisis. In light of these findings, the study underscores the importance of organizations adopting digital communication strategies based on genuine dialogue and interaction with their audiences across digital platforms. This has a significant impact on building trust and enhancing the organization's public image in the contemporary media landscape.
Keywords: Strategic Digital Communication; Corporate Crisis Management; Corporate Image; Digital Media; Conversational Communication; Social Media; Corporate Reputation